Analyses of cement composites with the addition of quarry dust as partial sand replacement materials
The development of cement composites has been proposed for many decades to fulfil the requirements in the construction sector and became one of the major producers of waste and source depletion, especially river sand. Quarry dust became an alternative material in cement composites to reduce the consumption of river sand and ecology rehabilitation in order to promote sustainable development of the construction industry. Therefore, this research was conducted to study the effects of quarry dust as partial sand replacement material on physical, mechanical and durability properties of the cement composites. In relation to this, the cement composites were categorised into two main sections. First section is the proportioning study that investigates the effect of quarry dust on the physical and mechanical properties, crack profile, fracture and surface morphology of cement composites under pressure load. In this study, the fabrication of cement composites was carried out by substituting quarry dust with a portion of river sand according to the various percentages at constant water cement ratio (0.45). The cement composites were produced from a mixture of ordinary Portland cement (OPC), river sand, quarry dust and water. Five different ratios of 1: 1.00: 0.00, 1: 0.90: 0.10, 1: 0.875: 0.125, 1: 0.850: 0.150 and 1: 0.825: 0.175 (cement: river sand: quarry dust) were prepared according to the related standards. The cement composites were cured in water for 7 and 28 days, and tested to determine the mechanical properties such as compressive strength and modulus of rupture, physical properties such as density, water absorption and moisture content. The other section is the durability study, which was conducted to observe the length change of cement composites when subjected to sulphate attack with the addition of 12.5 wt.% and 17.5 wt.% of the quarry dust.